2008
DOI: 10.1007/s11746-008-1219-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Polymorphic Transformations on Gelation of Tripalmitin Solid Lipid Nanoparticle Suspensions

Abstract: Solid lipid nanoparticle (SLN) suspensions, which consist of submicron-sized crystalline lipid particles dispersed within an aqueous medium, can be used to encapsulate, protect and deliver lipophilic functional components. Nevertheless, SLN suspensions are susceptible to particle aggregation and gelation during their preparation and storage, which potentially limits their industrial utilization. In this study, we examined the aggregation and gelation behavior of SLN suspensions composed of 10 wt% tripalmitin p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
94
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(105 citation statements)
references
References 41 publications
(57 reference statements)
9
94
1
1
Order By: Relevance
“…This phenomenon can be described by polymorphic transformation of the inner lipid matrix of NLCs. Jenning et al reported that the low temperature could induce the polymorphic transition of MCT from the amorphous form ( -form) to crystallized form ( -form), leading to the transformation of spherical to platelet shaped particles [26,27]. In addition, Helgason et al stated that the surfactants required to cover and stabilize the newly created interfaces may not be able to diffuse rapidly enough to adsorb at the newly formed lipid crystalline interfaces, leading to increased mean particle size due to flocculation [28].…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon can be described by polymorphic transformation of the inner lipid matrix of NLCs. Jenning et al reported that the low temperature could induce the polymorphic transition of MCT from the amorphous form ( -form) to crystallized form ( -form), leading to the transformation of spherical to platelet shaped particles [26,27]. In addition, Helgason et al stated that the surfactants required to cover and stabilize the newly created interfaces may not be able to diffuse rapidly enough to adsorb at the newly formed lipid crystalline interfaces, leading to increased mean particle size due to flocculation [28].…”
Section: Discussionmentioning
confidence: 99%
“…Lipid particles may retain an approximately spherical shape, or they may undergo appreciably changes in morphology depending on the cooling rate, holding temperature, oil type, and emulsifier type. These changes in particle morphology can lead to drastic changes in the rheology and stability of lipid nanoparticle suspensions [61,62].…”
Section: Physical State: Controlling Temperature or Solvent Qualitymentioning
confidence: 99%
“…The microstructure of SLN suspensions was also observed using an optical microscope (Nikon microscope Eclipse E400, Nikon, Japan). 29 …”
Section: Visual Observation and Microscopymentioning
confidence: 99%
“…[25][26][27][28] We recently investigated the mechanism of gelation in tripalmitin SLN suspensions and found that the incidence of gelation at different storage temperatures was associated with a polymorphic transition to the β-form, which increased the overall particle surface area and promoted particle aggregation through hydrophobic attraction of lipids at surfactant-free patches. 29 To make stable SLN suspensions for the encapsulation and protection of sensitive bioactive ingredients, it is necessary to either retard the polymorphic transition or to control the aggregation stability. 24 There have been many studies on modification of the crystallization and polymorphic behavior and stability of lipids in emulsions as well as SLN by varying surfactants, 19,20,[30][31][32][33][34][35] lipid composition, 36 particle size and distribution, 30,37,38 aqueous phase composition, and application of shear.…”
Section: Introductionmentioning
confidence: 99%